1993
DOI: 10.1021/jf00025a004
|View full text |Cite
|
Sign up to set email alerts
|

Milling quality of soybean cultivars as a function of premilling heat treatment and grain characteristics

Abstract: Ten varieties of soybean given two drying treatments, i.e., oven drying and dry heat roasting, were evaluated for their milling characteristics. Of 10 varieties, the cultivare PK-472, Alankar, and PK-564 yielded more than 80% dehulled splits (commonly known as dal), minimum undehulled grain percentage, and minimum milling losses and, therefore, were grouped as easy to mill varieties. The varieties PK-308 and T-49 yielded less milling percentage, maximum undehulled grain percentage, and milling losses and so we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The sand roasting was one of the pretreatments given to nuts prior to decortication, where nuts (water soaked and shed dried) were roasted at 60 C for 20 min. The nuts were dried under the shade for 1 hr after the soaking and then subjected to sand roasting pre-treatment (Chadha, 2001;Sachan, Chauhan, Suresh, Singh, & Verma, 1993 Tables 2 and 3. The study showed that the chironji nuts had average geometric mean diameter of 8.74 ± 0.02, which is at par with studies conducted by Kumar, Prabhakar, Srivastav, and Bhowmick (2014), Kumar et al (2016), and Deshmukh, Dange, Pardeshi, and Borkar (2017).…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…The sand roasting was one of the pretreatments given to nuts prior to decortication, where nuts (water soaked and shed dried) were roasted at 60 C for 20 min. The nuts were dried under the shade for 1 hr after the soaking and then subjected to sand roasting pre-treatment (Chadha, 2001;Sachan, Chauhan, Suresh, Singh, & Verma, 1993 Tables 2 and 3. The study showed that the chironji nuts had average geometric mean diameter of 8.74 ± 0.02, which is at par with studies conducted by Kumar, Prabhakar, Srivastav, and Bhowmick (2014), Kumar et al (2016), and Deshmukh, Dange, Pardeshi, and Borkar (2017).…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…Laboratory studies on dehulling efficiency of pulses have used many devices such as the Tangential Abrasive Dehulling Device (Reichert et al 1986 ;Singh et al 1992a) which measures yield of seed coat. Swamy et al (1991) and Sachan et al (1993) used a Satake laboratory mill in studies on Red Gram and soybean, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Early trials in this laboratory found that the Satake device could be used for both decortication and splitting of Ðeld peas in a very short time. Preconditioning of the seeds before processing to make decortication easier has been accepted for many pulses (Swamy et al 1991 ;Sachan et al 1993) but little appears to have been reported on preconditioning of Ðeld peas. Therefore, the present work was undertaken to study the e †ects of physical grain characteristics and preconditioning on the dehulling efficiency of Australian Ðeld peas.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies on dehulling efficiency of pulses have used many devices such as the Tangential Abrasive Dehulling Device (Reichert et al 1986 ;Singh et al 1992a) which measures yield of seed coat. Swamy et al (1991) and Sachan et al (1993) used a Satake laboratory mill in studies on Red Gram and soybean, respectively. Early trials in this laboratory found that the Satake device could be used for both decortication and splitting of Ðeld peas in a very short time.…”
Section: Introductionmentioning
confidence: 99%